Relationships between muscle strength, lung function, and cognitive function in Chinese middle-aged and older adults: A study based on the China health and retirement longitudinal study (CHARLS) - Yixuan Ma; Xinze Wu; Yinjiao Zhao; Weihao Hong; Yisheng Luan; Peiyu Song; Bing Zhang (Journal of the Formosan Medical Association)
Objective: As the population ages, concerns about cognitive decline have become increasingly relevant in medical consultations. This study aims to analyze the interaction between muscle strength, lung function, and cognitive function in Chinese middle-aged and older adults, providing a theoretical basis for better prevention of cognitive decline. Methods: This study used data from the China Health and Retirement Longitudinal Study (CHARLS) wave 3, including 13 716 participants aged 45 years or older. Cognitive function was assessed through two dimensions, resulting in a total score ranging from 0 to 31 points, with higher scores indicating better cognitive function. Muscle strength was measured using normalized grip strength and chair-standing time, while lung function was evaluated using peak expiratory flow (PEF). Results: Total cognitive function scores exhibited significant correlations with grip strength, chair-standing time, and PEF. Muscle strength and lung function demonstrated significant associations with cognitive function, with lung function emerging as a notable mediating factor. This relationship persisted even after adjusting for potential confounding variables. Specifically, PEF played a substantial mediating role in linking grip strength to cognitive function scores (estimated indirect effect = 0.0132, boot-strapped standard error = 0.0015, boot-strapped standard 95% confidence interval = 0.0104, 0.0162). Additionally, PEF served as a significant mediator in the association between chair-standing time and cognitive function scores (estimated indirect effect = −0.0204, boot-strapped standard error = 0.0023, boot-strapped standard 95% confidence interval = −0.0251, −0.0159). Conclusion: The study highlights the importance of addressing declines in muscle strength and lung function to identify risk factors associated with cognitive function. Understanding these relationships can provide insights into potential pathways linking these variables and may aid in better prevention of cognitive decline. Further long-term longitudinal cohort studies are needed to explore the causality between these factors.